Prospects for the Development of Ecological Tourism in Specially Protected Natural Areas of the Ulyanovsk Region - PROVALOVA, Elena V.; LUKIYANOVA, Marina N.; SKROBOTOVA, Olga V.; IVANOVA, Raisa M. (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).11, 2019)
The development and improvement of the system of specially protected natural territories of the Russian Federation is considered to be among the main directions of the state environmental policy, which makes the study relevant. The article discusses the existing network of specially protected natural territories of the Ulyanovsk region, identifies problems of its existence and possible ways to eliminate them, as well as prospects for the development of a network of specially protected natural territories of federal, regional and local importance. The concept of eco-tourism is considered, the criteria by which tourism is defined as ecological are determined. It is concluded that protected areas are able to take over planning, management and monitoring functions of ecotourism activities. Ecotourism can be an effective means of environmental education and can draw the attention of the general public to environmental issues and increase public support for protected areas.